2008
DOI: 10.1001/archneurol.2007.14
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Alpers Disease

Abstract: Background: Alpers disease is commonly associated with polymerase ␥ deficiency and usually affects infants or young children. Objective: To report a juvenile case of Alpers disease due to mutations in the polymerase ␥ gene (POLG1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 20 publications
3
33
0
2
Order By: Relevance
“…Several reports have shown that patients with POLG mutations and Alpers–Huttenlocher syndrome present with syndromic epilepsy with occipital lobe predilection. 5,21,2325 In addition, our patient population (Table 1) and recent literature demonstrates seizure semiology consistent with occipital lobe epileptic discharges; focal clonic motor seizures, secondarily generalized tonic–clonic seizures, hallucinations and nystagmus. 2325,28 However, early studies have not consistently shown occipital lobe discharges, with some describing generalized discharges, hypsarrhythmia or multifocal discharges.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Several reports have shown that patients with POLG mutations and Alpers–Huttenlocher syndrome present with syndromic epilepsy with occipital lobe predilection. 5,21,2325 In addition, our patient population (Table 1) and recent literature demonstrates seizure semiology consistent with occipital lobe epileptic discharges; focal clonic motor seizures, secondarily generalized tonic–clonic seizures, hallucinations and nystagmus. 2325,28 However, early studies have not consistently shown occipital lobe discharges, with some describing generalized discharges, hypsarrhythmia or multifocal discharges.…”
Section: Discussionsupporting
confidence: 74%
“…5,21,2325 In addition, our patient population (Table 1) and recent literature demonstrates seizure semiology consistent with occipital lobe epileptic discharges; focal clonic motor seizures, secondarily generalized tonic–clonic seizures, hallucinations and nystagmus. 2325,28 However, early studies have not consistently shown occipital lobe discharges, with some describing generalized discharges, hypsarrhythmia or multifocal discharges. 28,29 Tulinius and Hagne 28 suggested that timing of the disease progression was likely responsible for EEG variation.…”
Section: Discussionsupporting
confidence: 74%
“…The function of these mutations remains unclear, while the p.A862T mutation affects the polymerase domain. Another polymerase domain mutation, c.3139C>T/p.R1047W, has recently been described in juvenile Alpers syndrome,17 while a sixth novel substitution, c.32G>A/p.G11D, is located in the leader sequence involved in directing the protein to the mitochondrion and warranted further investigation. Multiple conservation alignments show that all of the substitutions affect amino acids which are highly conserved across species (fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…The side chain substitutions G848S, T851A, R852C, and R853Q are located in a conserved region of the thumb domain, and all are associated with Alpers syndrome [50,66,74,75]. In each case, the mutations were shown to nearly eliminate polymerase activity [76].…”
Section: Pol γ and Mtdna Replication Proteins In Diseasementioning
confidence: 99%